Plethysmographic variability index as a tool to assess fluid responsiveness in critically ill patients: a correlation study with inferior vena cava distensibility index - Bedi, Parvinder Singh; Pahwa, Bhavna; Hooda, Bhavna; Dwivedi, Deepak (International Journal of Research in Medical Sciences, 2019)
Background: In critically ill patients in the intensive care unit (ICU), early aggressive fluid replacement is the cornerstone of resuscitation. Traditionally employed static measures of fluid responsiveness have a poor predictive value. It is therefore imperative to employ dynamic measures of fluid responsiveness that take into account the heart lung interactions in the mechanically ventilated patients. The main objective of this study was to evaluate the reliability of one such non-invasive dynamic index: Plethysmographic variability index (PVI) compared to the widely employed Inferior vena cava distensibility index (dIVC). Methods: Seventy-six adult patients admitted at a tertiary care mixed ICU, who developed hypotension (MAP<65mmHg), were included in the study. PVI was recorded using the MASIMO-7 monitor and dIVC measurements done using Terason ultrasound. Based on the dIVC measurement threshold of 18%, the patients were classified into volume responders and non-responders. The hemodynamic, PVI and dIVC measurements were recorded at pre specified time points following a fluid challenge of 20 ml/kg crystalloid infusion. Results: Baseline PVI values were significantly higher in the responders (22.3±8.2) compared to non-responders (10.1±2.9) (p<0.001) and showed a declining trend at all time points in the responders. Similar declining trend was observed in the dIVC measurements. Overall, the Pearson correlation graph showed strong correlation between dIVC and PVI values at all time points (r=0.678, p=0.001). The ROC curve between the dIVC and PVI values revealed that Baseline PVI (Pre PVI) >15.5% discriminated between responders and non-responders with a 90.2% sensitivity and 75% specificity with an AUC of 0.84 (0.72-0.96) (p<0.001). Conclusions: There is good correlation between PVI values and measured dIVC values at baseline and following a fluid challenge. Thus, PVI may be an acceptable, real time, continuous, surrogate measure of fluid responsiveness in critically ill patients.